2023
DOI: 10.15252/emmm.202318014
|View full text |Cite
|
Sign up to set email alerts
|

LRP8‐mediated selenocysteine uptake is a targetable vulnerability in MYCN‐amplified neuroblastoma

Abstract: Ferroptosis has emerged as an attractive strategy in cancer therapy. Understanding the operational networks regulating ferroptosis may unravel vulnerabilities that could be harnessed for therapeutic benefit. Using CRISPR‐activation screens in ferroptosis hypersensitive cells, we identify the selenoprotein P (SELENOP) receptor, LRP8, as a key determinant protecting MYCN‐amplified neuroblastoma cells from ferroptosis. Genetic deletion of LRP8 leads to ferroptosis as a result of an insufficient supply of selenocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…However, it remains to be elucidated which of those pathways are conserved in specific tissues and cell types. We and others have previously showed that selenium deprivation and uptake inhibition sensitizes to ferroptosis selectively when cells are cultured at low density 23,24,34 . Here we demonstrate that in triple-negative breast cancer (TNBC) cells, the seeding density positively regulates the expression of genes involved in fatty acid synthesis and desaturation (i.e.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, it remains to be elucidated which of those pathways are conserved in specific tissues and cell types. We and others have previously showed that selenium deprivation and uptake inhibition sensitizes to ferroptosis selectively when cells are cultured at low density 23,24,34 . Here we demonstrate that in triple-negative breast cancer (TNBC) cells, the seeding density positively regulates the expression of genes involved in fatty acid synthesis and desaturation (i.e.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, GPX4 inhibition in combination with immunotherapy showed promising results in murine models of TNBC 42 . While selenium-deprived diets have not been tested in breast cancer models, Eagle et al showed a therapeutic effect of selenium deprivation in leukaemia models, while Alborzinia et al inhibited cellular selenoprotein P uptake to decrease the expression of selenoproteins and induce ferroptosis in neuroblastoma 22,24 .…”
Section: Carlisle Et Al Have Shown That High Sephs2 Expression Correl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have identified the LRP8/SELENOP axis as responsible for selenocysteine uptake inside the cell and SCLY for its recycling, therefore the inhibition of this pathway can promote ferroptosis. [20] Angeli and coworkers also identified a new regulator of selenium metabolism as a regulator of ferroptosis, which also appears to act by maintaining the stability of GPX4. It exhibits a very stable sulfenic acid group that interacts with hydrogen selenide anion to provide a new potential selenium donor.…”
Section: Pedro Angeli: Deciphering Selenium Uptake: Implications For ...mentioning
confidence: 99%
“…Selenium can be absorbed as inorganic form (SeO 3 2− ) and organic forms (selenocysteine). Recent studies have identified the LRP8/SELENOP axis as responsible for selenocysteine uptake inside the cell and SCLY for its recycling, therefore the inhibition of this pathway can promote ferroptosis [20] . Angeli and coworkers also identified a new regulator of selenium metabolism as a regulator of ferroptosis, which also appears to act by maintaining the stability of GPX4.…”
Section: Introductionmentioning
confidence: 99%